Irreversibility characteristics of a modified microchannel heat sink operated with nanofluid considering different shapes of nanoparticles. (April 2020) - Bahiraei, Mehdi; Monavari, Ali; Naseri, Mohammad; Moayedi, Hossein
Highlights: Effects of water–Al2 O3 nanofluid on second law characteristics in the microchannel heat sink. The nanofluid is considered with different nanoparticle shapes. Oblate spheroid nanoparticles lead to the highest entropy generation rate. Greater Reynolds numbers and nanofluid with the platelet-shaped nanoparticles are optimal. Bejan number decreases by rising Reynolds number, and has its smallest value for platelet nanoparticles. Abstract: In the current paper, the influences of the water–boehmite alumina nanofluid with various nanoparticle shapes on the second law attributes in the microchannel heat sink are analyzed. This assessment is carried out for five nanoparticle shapes (i.e., platelet, cylinder, blade, brick, and oblate spheroid) at four Reynolds numbers (i.e., Re = 300, Re = 800, Re = 1300, and Re=1800). Furthermore, the concentration is considered constant equal to 1% for all the modes. For all the nanoparticle shapes, the thermal entropy generation is diminished and frictional entropy generation is augmented by rising the Re. The oblate spheroid nanoparticles result in the highest entropy generation followed by the brick, blade, cylinder, and platelet nanoparticle shapes, respectively. By the changes of the Re, the variations of the thermal entropy generation are low, but the frictional entropy generation has significant changes. The greater Re numbers and the nanofluid with the platelet-shaped nanoparticles are optimal because result in the lowest irreversibility. In the nanofluid having the platelet-shaped nanoparticles, the total entropy generation decreases 17.4% by rising the Re from 300 to 1800. Besides, the Bejan number declines by the increase of the Re, and has its smallest value for the platelet nanoparticles-based nanofluid. Besides, the difference among the Bejan numbers of the various nanoparticle shapes is more noticeable at larger Re numbers.